The C-MIC II Follow-Up Study: Safety and Efficacy Results 12 months After Deactivation of Cardiac Microcurrent Therapy - Jesus E Rame; Dragana N Kosevic; Tamara Kovacevic-Preradovic; Sasko Jovev; Marija Zdravkovic; Nermir Granov; Tanja Popov; Igor Rudez; Petar Vukovic; Velibor Ristic; Annette Holtdirk; Tim Friede; et al. (European Journal of Heart Failure, 2026)
Abstract Background The C-MIC II trial demonstrated benefits of 6 months of cardiac microcurrent (C-MIC) therapy in patients with non-ischemic heart failure with reduced ejection fraction (HFrEF). The prospective C-MIC II Follow-Up Study evaluates safety and efficacy outcomes post-device deactivation. Methods Primary safety-related endpoints included all-cause, cardiovascular and device-related mortality and hospitalizations and adverse events (AEs). Secondary efficacy-related endpoints included changes in left ventricular ejection fraction (LVEF), Kansas City Cardiomyopathy Questionnaire Overall Summary Score (KCCQ-OSS), 6-minute walk distance (6MWD), New York Heart Association (NYHA) class and device reactivation rate. Here, we report 12-month results comparing the 6-month time-point (at the end of active therapy) with the 18-month time-point (12 months post-deactivation). Results Of 32 eligible patients, 31 (97%) were enrolled. At 12 months post-device deactivation, 3 patients (10%) were hospitalized and 1 died (3%); none were device-related. One device-related AE occurred and resolved completely. Improvements in LVEF (vs pre-implantation: +6%; 95% CI 5–8; p<0.0001) and KCCQ-OSS (vs pre-implantation: +43 points; 95% CI 36–49; p<0.0001) were sustained and unchanged from 6 months (LVEF: -0.1%; 95% CI -2–2; p=0.87; KCCQ-OSS:-2; 95% CI -8–4; p=0.49). The 6MWD remained improved (vs pre-implantation: +150 m; 95% CI 109–191; p<0.0001), with a modest decrease (-31 m; 95% CI -56– -7; p=0.013) from 6 months. Improvements in NYHA class (≥1-class improvement in 77% patients) were sustained. Three (10%) patients required device reactivation. Conclusion Among patients previously treated with C-MIC device, improvements in LVEF, 6MWD, NYHA class and KCCQ-OSS were sustained, with a favorable safety profile 12 months post-deactivation.